The fight within : effects of impulsivity and executive function on competitive gambling and targeted physical aggression - Gan, Ruth Ying Teng (2017)
This paper investigated the effects of competitive gambling on targeted physical aggression. In particular, it explored the mediating effect of frustration on gambling outcomes and physical aggression. Specifically, we hypothesised that losers would be more aggressive than winners because they felt more frustrated. Additionally, we proposed that the role of the individual’s executive function and impulsivity trait could be a potential moderator of the mediating effect of frustration. Seventy-six university undergraduates, most of whom were recreational gamblers, took part in a simulated competitive gambling task in which some participants were manipulated to win and others were manipulated to lose. The hot sauce paradigm was employed as a measure of targeted physical aggression. Participants also had to complete a measure of impulsivity and three tests of executive function, namely, the Stroop Task, the Corsi Block Tapping Task and the Wisconsin Card Sorting Test. Results indicated that losers were more frustrated than winners. Other relationships were found to be non-significant. We discussed the possible reasons behind our results and explored potential limitations of our study. Keywords: Gambling outcomes, frustration, physical aggression, executive function, impulsivity